Pembangunan Kultur Good Governance Melalui Pendidikan Islam - Rahmat Hidayat; Kasful Anwar US; Sya'roni Sya'roni (Jurnal Budi Pekerti Agama Islam, 2024)
This research discusses the Development of Good Governance Culture Through Islamic Education. The implementation of government in good governance is related to the issue of transparency, public accountability, and so on. Conceptually, it can be understood that good governance reflects a process that gives control to the community over its economy. Its institutions and social and political resources are used not only for development, but also to create integration for the welfare of the people. Good governance is also understood as the implementation of solid and responsible government that is in line with the principles of democracy and the market, efficient government, and government that is free and clean from corruption, collusion, and nepotism (KKN) activities. Democracy, morality, and creative-critical thinking are values that need to be developed and instilled in creating a culture of good governance. Through education, these values are instilled and transformed into the culture of the community. The education of these values is not just cognitive knowledge, but becomes integral in the personality of the younger generation, the future leader of the nation.